2008
DOI: 10.30541/v47i1pp.1-26
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Dividend or Demographic Threat in Pakistan?

Abstract: Population growth and size have remained the focus of debate for centuries but the recent demographic transition in developing countries has made social scientists take note of the changing age structure of the population as well. As a result of declining population growth and consequent changes in age structure, the proportion of working-age population is increasing in most developing countries. An associated decline in the dependent age population offers a window of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…They found that demographic dividend is more prominent in East Asia as income per effective consumer has increased by 12.5%, while the impact of change in adult survival and youth dependency induced about 20% increase in saving rate. Nayab (2008) inspected the impact of demographic gift and its future implication for Pakistan from 1950 to 2050. Results showed that significant reduction in mortality rate was observed since 2006, while fertility rate had fallen from 6 children to 4.5 children to a woman by the year 2000 and it would reach at 1.69 children by the year 2050. analyzed the influence of demographic factors in amplifying economic growth in Asia while focusing more on East Asia from 1960 to 2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that demographic dividend is more prominent in East Asia as income per effective consumer has increased by 12.5%, while the impact of change in adult survival and youth dependency induced about 20% increase in saving rate. Nayab (2008) inspected the impact of demographic gift and its future implication for Pakistan from 1950 to 2050. Results showed that significant reduction in mortality rate was observed since 2006, while fertility rate had fallen from 6 children to 4.5 children to a woman by the year 2000 and it would reach at 1.69 children by the year 2050. analyzed the influence of demographic factors in amplifying economic growth in Asia while focusing more on East Asia from 1960 to 2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A seminal article by Durr-e- Nayab (2006) showed that Pakistan was passing through a demographic transition, which in turn could yield a demographic dividend. The article marked a turning point in the way population and labor force issues were treated in the broader context of the country's development prospects, economic plans, and growth strategy.…”
Section: " "mentioning
confidence: 99%
“…4.2 and 4.3 show the expected size and duration of the demographic dividend based on two alternative estimates. These include revised estimates byNayab (2006) based on the UN 2010 Population Projection (UN 2011) and the Population Council estimates presented in Chapter 2. The updated projections show that the demographic dividend started not at the end of the 1980s, asNayab (2006) earlier proposed, but was delayed to the early or mid-1990s.…”
mentioning
confidence: 99%
See 2 more Smart Citations